Immigration Policy in the European Union: Opportunities, Challenges and Dilemmas - Anna Yulia Hartati (Proceeding Of The International Seminar and Conference on Global Issues, 2016)
This article describes the immigration policy dilemma in the European Union. Immigration Issues strengthened along with the wave of migrants to Europe. This raises a problem that is quite complex. The phenomenon of immigration is causing changes in the European countries. One important factor that has changed is the policy. On the one hand, the provision of legal migration program of the government in the recipient country is very limited because European countries now also perform a special selection to filter the migrants who have high skills. The existence of this screening program indicative of the problems of the workers and the short-term discrepancies between supply and demand in many European countries. The existence of various problems related to immigrants eventually led to a dilemma in policy making on immigration in the European Unio n. This dilemma can be divided into four categories, including a dilemma: labor migration policy, migration control policies, protection and asylum systems, as well as integration policy. The author uses the research methods used to use the analysis of qualitative research, which the authors create a description, picture or painting in a systematic, factual, accurate information on the facts, nature and the relationship between the phenomenon investigated.Keywords: immigration policy, labor migration, protection and asylum systems, policy dilemma